Association of Low Hourly Wages in Middle Age With Faster Memory Decline in Older Age: Evidence From the Health and Retirement Study. Issue 12 (21st September 2022) - Kezios, Katrina L; Zhang, Adina; Kim, Soohyun; Lu, Peiyi; Glymour, M Maria; Elfassy, Tali; Al Hazzouri, Adina Zeki
Abstract: Little research has investigated the long-term relationship between low wages and memory decline, despite the growing share of low-wage workers in the US labor market. Here, we examined whether cumulative exposure to low wages over 12 years in midlife is associated with memory decline in later life. Using 1992–2016 data from the Health and Retirement Study, we analyzed data from 2, 879 individuals born in 1936–1941 using confounder-adjusted linear mixed-effects models. Low-wage work was defined as an hourly wage lower than two-thirds of the federal median wage for the corresponding year and was categorized into "never, " "intermittent, " and "sustained" based on wages earned from 1992 to 2004. Memory function was measured at each study visit from 2004 to 2016 via a memory composite score. The confounder-adjusted annual rate of memory decline among "never" low-wage earners was −0.12 standard units (95% confidence interval: −0.13, −0.10). Compared with this, memory decline among workers with sustained earning of low midlife wages was significantly faster (βtime×sustained = −0.014, 95% confidence interval: −0.02, −0.01), corresponding to an annual rate of −0.13 standard units for this group. Sustained low-wage earning in midlife was significantly associated with a downward trajectory of memory performance in older age. Enhancing social policies to protect low-wage workers may be especially beneficial for their cognitive health.